Enterprise Strategic Management From the Perspective of Business Ecosystem Construction Based on Multimodal Emotion Recognition - Bi, Wei; Xie, Yongzhen; Dong, Zheng; Li, Hongshen (Frontiers in Psychology, 2022)
Emotion recognition is an important part of building an intelligent human-computer interaction system and plays an important role in human-computer interaction. Often, people express their feelings through a variety of symbols, such as words and facial expressions. This paper aims to study a multimodal emotion recognition method based on attention mechanism. It analyzes the current emotional state of consumers and the development direction of enterprises through multi-modal emotion recognition of human emotions and analysis of market trends, so as to provide the most appropriate response or plan. This paper firstly describes the related methods of multimodal emotion recognition and deep learning in detail, and briefly outlines the meaning of enterprise strategy in the business ecosystem. Then the scheme design of multimodal emotion recognition based on self-attention mechanism is carried out. Through the comparative analysis of the accuracy of single-modal and multi-modal emotion recognition, the self-attention mechanism is applied in the experiment. The experimental results show that the average recognition accuracy of happy under multimodal emotion recognition reaches 91.5%.